Cultural Sensitivity and Teaching Competence: Examining Thai Students’ Satisfaction with Non-Native English-Speaking Teachers - Lemana II, Henry E.; Waluyo, Budi; Ahmad, Crizjale V. (Journal of Education Culture and Society, 2025)
Aim. Despite the growing presence of non-native English-speaking teachers (NNESTs) in English as a Foreign Language (EFL) classroom, little is known about how their teaching impacts student satisfaction, motivation, and confidence. While much of the existing research focuses on comparisons between native and non-native teachers, this study shifts the focus to how Thai students perceive NNESTs’ teaching competence, communication skills, English proficiency, and pedagogical strategies. It also explores how these perceptions influence students’ engagement and willingness to use English. Method. This qualitative study was conducted at an autonomous university in southern Thailand, where students were randomly assigned to either native or non-native English-speaking teachers. A phenomenological approach was used to examine the experiences of 432 second-year students who had been taught by NNESTs for at least one full academic year. Reflective essays were collected, allowing students to share their insights on classroom interactions, teaching methods, and overall satisfaction. Data were analysed thematically to identify key patterns in student experiences. Results. Students valued NNESTs for their structured lessons, clear explanations, encouragement, and ability to relate to the challenges of learning English. Most students felt that NNESTs’ cultural insights and supportive teaching styles created an engaging and comfortable learning environment. However, some students struggled with fast-paced instruction, accent variations, and repetitive teaching approaches, which occasionally made learning difficult. Effective NNESTs were those who adapted their teaching methods, provided constructive feedback, and fostered a classroom atmosphere where students felt comfortable making mistakes. Conclusion. The findings indicate that students place greater emphasis on teaching quality and cultural sensitivity than on native-speaker status, which points to the importance of professional development programs that strengthen NNESTs’ instructional flexibility and communicative competence.